2013
DOI: 10.1093/humrep/det062
|View full text |Cite
|
Sign up to set email alerts
|

Updated ultrasound criteria for polycystic ovary syndrome: reliable thresholds for elevated follicle population and ovarian volume

Abstract: This study was funded by Cornell University and fellowship awards from the Saskatchewan Health Research Foundation and Canadian Institutes of Health Research. The authors have no conflict of interests to disclose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
123
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(135 citation statements)
references
References 28 publications
9
123
0
3
Order By: Relevance
“…A subset of participants evaluated in this study was used to develop revised sonographic criteria for polycystic ovarian morphology as described previously. 13 …”
Section: Participantsmentioning
confidence: 99%
“…A subset of participants evaluated in this study was used to develop revised sonographic criteria for polycystic ovarian morphology as described previously. 13 …”
Section: Participantsmentioning
confidence: 99%
“…Ponadto, stosowanie aparatów ultrasonograficznych o wysokiej rozdzielczości umożliwia dokładniejszą ocenę puli pęcherzyków jajnikowych. Skłania to do zmiany kryterium liczby pęcherzyków jajnikowych z 12 (wg kryteriów rotterdamskich z 2003 r.) do 19 bądź 25 [4,51]. Lauritsen i wsp.…”
Section: Amh W Diagnostyce Pcosunclassified
“…Early comparative studies showed intra and interobserver variations in the two-dimensional (2D) transvaginal AFC in the general population and a 12 to 13% rate of underestimation in the exact number of antral follicles present within the ovary, 11 however, recent studies, using new three-dimensional (3D) US modes, increase this underestimation rate up to 20 to 30%. [12][13][14][15][16][17]22 Besides this limitation, and in order to maintain standard criteria for research purposes, 2D transvaginal scan remains as the recommended method for antral follicle count in the general population including PCOS patients, and the count of at least 12 follicles remains the limit to categorize a polycystic appearance ovary. 6 Herein, we describe several and modern 3D ultrasound modes for the study of PCOS-related ovarian morphology; these new methods are scarcely mentioned on the medical literature since the clinical experience is limited; further, they are sometimes described as 'future techniques'.…”
Section: Ultrasound Criteria Including State-of-the-art 3d Visualizatmentioning
confidence: 99%
“…16,17,21,22 Recent publications focused on PCOS patients showed a mean number of AFC of 19 to 26 follicles. 12,13,28 This situation has arisen from the marked improvements in the level of spatial resolution afforded by newer ultrasound scanners. Ovarian volume or area (OA) were also included as mandatory diagnostic criteria by ESHRE.…”
Section: Fig 13mentioning
confidence: 99%